Cigarette smoke-induced accumulation of lung dendritic cells is interleukin-1α-dependent in mice - Botelho, Fernando M (BioMed Central, 2012)
BACKGROUND: Evidence suggests that dendritic cells accumulate in the lungs of COPD patients and correlate with disease severity. We investigated the importance of IL-1R1 and its ligands IL-1α and β to dendritic cell accumulation and maturation in response to cigarette smoke exposure. METHODS: Mice were exposed to cigarette smoke using a whole body smoke exposure system. IL-1R1-, TLR4-, and IL-1α-deficient mice, as well as anti-IL-1α and anti-IL-1β blocking antibodies were used to study the importance of IL-1R1 and TLR4 to dendritic cell accumulation and activation. RESULTS: Acute and chronic cigarette smoke exposure led to increased frequency of lung dendritic cells. Accumulation and activation of dendritic cells was IL-1R1/IL-1α dependent, but TLR4- and IL-1β-independent. Corroborating the cellular data, expression of CCL20, a potent dendritic cells chemoattractant, was IL-1R1/IL-1α-dependent. Studies using IL-1R1 bone marrow-chimeric mice revealed the importance of IL-1R1 signaling on lung structural cells for CCL20 expression. Consistent with the importance of dendritic cells in T cell activation, we observed decreased CD4(+) and CD8(+) T cell activation in cigarette smoke-exposed IL-1R1-deficient mice. CONCLUSION: Our findings convey the importance of IL-1R1/IL-1α to the recruitment and activation of dendritic cells in response to cigarette smoke exposure.